IndigiQueer the Space: An Interview with Ty Defoe - Gareiss, Nic (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
Ty Defoe is an Oneida and Ojibwe interdisciplinary artist. This contribution includes a video entitled “Circle” and an interview with Nic Gareiss, in which Defoe discusses the ways in which he has worked to Indigenize, decolonize, and queer a variety of spaces, including online digital spaces, during the pandemic.